ANGIOGENESIS MODULATION AS AN EFFICIENT METHOD TO TREAT THE EXPERIMENTAL DIABETIC RETINOPATHY - Preys, N.I.; Savytskyi, I.V.; Hrytsan, I.I.; Tiron, O.I.; Vyshnevska, H.O.; Kuvshinova, I.I.; Lyashevska, O.O. (World of Medicine and Biology, 2024)
The purpose of the study was to investigate the changes in blood vascular endothelial growth factor levels in experimental animals with diabetic retinopathy modeling using the ways of its pharmacological correction. Experimental studies were performed on the model of streptozotocin-induced diabetes mellitus on Wistar rats which were randomized on seven groups in dependence of separate and combined pharmacological compounds administration to treat the experimental diabetic retinopathy features. The vascular endothelial growth factor level in the blood serum of rats was determined on 30, 60 and 180 days of the trials. The data obtained confirm the development of diabetic retinopathy in conditions of streptozotocin model of diabetes mellitus. Diabetic retinopathy development characterized by vascular endothelial growth factor content in rats blood increase with the top level of increase on the 180th day of the trials. The expressed positive effect of vascular endothelial growth factor level normalization was observed in case of aflibercept, L- arginine and citicoline combined administration. The authors stressed on immune mechanisms pathogenetic role in diabetic retinopathy. Determination of vascular endothelial growth factor principal pathogenetic role in diabetic retinal tissue damage opened a new direction of diabetic retinopathy targeted pathogenetically determined pharmacocorrection by blocking the vascular endothelial growth factor signaling pathway. The established immune mechanisms involvement into diabetic retinopathy pathogenetic mechanisms by blood vascular endothelial growth factor level increase is an experimental background of reasonability of vascular endothelial growth factor both synthesis and/or activity block in clinical conditions.